GRANULOMETRIC COMPOSITION CHARACTERISTICS OF THE TYPICAL IRRI-GATED GRAY SOILS OF PISKENT DISTRICT (Scientific journal of the Fergana State University, 2026)
This article extensively addresses the issues related to assessing the fertility level of typical irrigated gray soils. During the study, the mechanical composition, agrochemical, and agrophysical properties of the typical irrigated gray soils in Piskent district of Tashkent region were thoroughly analyzed. In the evaluation process, important factors such as nutrient content and soil structure condition were taken into account to determine soil fertility. Soil quality levels were also considered based on the bonitet score. In agriculture, achieving high yields and successful crop cultivation is closely linked to the mechanical composition of the soil. The quality and productivity of crops require adaptation to soil conditions, making it essential to study the soil properties of each region. Comprehensive scientific research was conducted in the typical gray soils spread in Piskent district of Tashkent region to determine the effect of microelements on crop development. The study employed not only the N.A. Kachinskiy method but also the international standards “ISO/TC 190 Soil quality” to determine soil mechanical composition. The research results are of significant importance for creating a scientific basis to increase, preserve, and efficiently utilize the fertility of irrigated soils.